Virtuous circle: Human capital and human resource management in social enterprises - Roumpi, Dorothea; Magrizos, Solon; Nicolopoulou, Katerina (Human Resource Management, 2020)
AbstractThe majority of the extant research on human resource management (HRM) draws conclusions based on evidence from for‐profit organizations. In response to calls for the exploration of HRM in different contexts, this study focuses on understanding HRM in the context of social enterprises. The unique context of social enterprises and their unique workforce raise questions about the direct applicability of frameworks developed from examining HRM in for‐profit organizations. The narratives provided by 20 CEOs, HR directors, and managers of social enterprises in the United Kingdom highlight the importance of “ethics of care” as the core of the HRM‐related decisions in the “third sector.” In addition, we identify five distinct workforce categories and propose a typology of differentiated HRM systems that enable social enterprises to achieve their dual mission. Finally, we propose a “virtuous circle” model, highlighting “ethics of care” as the main driver for organizational outcomes, using differentiated HRM systems that better serve their needs.